Global Exponential Stability and Stabilization of Fractional-Order Positive Switched Systems (International Journal of Innovative Research in Computer Science & Technology, 2017)
This paper is concerned with the global  exponential stability(GES) and stabilization of  fractional-order positive switched systems(FOPSS) with  average dwell time(ADT). Firstly, the the concept of  GES is extended to FOPSS. Then, by constructing  copositive Lyapunov functions and using ADT  approach, a state feedback controller is constructed,  and sufficient conditions are derived to guarantee that  the corresponding closed-loop system is globally  exponentially stable. Such conditions can be easily  solved by linear programming. Finally, an example is  given to demonstrate the effectiveness of the proposed  method.
Keywords: fractional-order positive switched systems; global exponential stability; average dwell time